The Effectiveness of Tiktok Application in Improving Regular Verb Learning among Tenth Grade Students of Vocational High School - Ibrahim, Maikhel Rusmana; Raihana, Esti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the effectiveness of the TikTok application in enhancing regular verb learning among tenth-grade students at Vocational High School (SMK) Negeri 6 Pekanbaru. A quasi-experimental research design was applied, involving two classes: an experimental class of 36 students, who used TikTok-based learning activities, and a control class of 36 students, who were taught using conventional methods. The research instrument consisted of a multiple-choice test. To determine significant differences between the two groups, statistical data analysis, including a paired sample t-test, was conducted. The results showed that the experimental class exhibited a notable improvement, with their post-test scores increasing from an average of 51.39 to 76.94, reflecting a gain of 25.55 points. Meanwhile, the control class, which followed traditional teaching methods, demonstrated only a minor improvement from 56.11 to 61.25. The significance level (sig. 2-tailed) of 0.000, which is lower than the standard alpha level of 0.05, confirmed that the alternative hypothesis (Ha) was accepted. These findings suggest that the TikTok application significantly enhances regular verb learning among tenth-grade students at SMK Negeri 6 Pekanbaru. Keywords: Regular verbs, TikTok, digital learning, language acquisition